Talking Stick: Hasil Belajar IPA Dan Kemampuan Kerjasama Siswa - Swastika Sari; Astuti Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to determine the influence of cooperative learning model type of talking stick to the results of science learning class vii students in smp n 5 banguntapan, bantul in 2016/2017 academic year in terms of cooperation ability. this study is quasi-experimental. techniques of collecting data using test techniques, questionnaires and documentation. the instrument test contains 30 multiple choice questions, and the questionnaire instrument contains 20 statements. the result, the researcher obtained fcount = 1.082 and p = 0.283, the average learning outcome was 21.75, the average questionnaire was 80.13. based on the average learning outcomes and questionnaires, then there is the influence of talking stick to the results of science learning grade vii students in terms of students' cooperation ability.